2021
DOI: 10.5194/isprs-archives-xliv-m-3-2021-1-2021
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Task Learning From Fixed-Wing Uav Images for 2d/3d City Modelling

Abstract: Abstract. Single-task learning in artificial neural networks will be able to learn the model very well, and the benefits brought by transferring knowledge thus become limited. In this regard, when the number of tasks increases (e.g., semantic segmentation, panoptic segmentation, monocular depth estimation, and 3D point cloud), duplicate information may exist across tasks, and the improvement becomes less significant. Multi-task learning has emerged as a solution to knowledge-transfer issues and is an approach … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…So, the representative and diverse task-oriented dataset is necessary part of machine learning study. A number of datasets exists (Bastani and Madden, 2021, Mohanty, 2018, Bayanlou and Khoshboresh-Masouleh, 2021, that are available for scientific community interested in semantic segmentation and image vectorization problems.…”
Section: Introductionmentioning
confidence: 99%
“…So, the representative and diverse task-oriented dataset is necessary part of machine learning study. A number of datasets exists (Bastani and Madden, 2021, Mohanty, 2018, Bayanlou and Khoshboresh-Masouleh, 2021, that are available for scientific community interested in semantic segmentation and image vectorization problems.…”
Section: Introductionmentioning
confidence: 99%
“…After different tests and analysis of the esults, has been shown that it is possible to replace the "classic method" of surveying via UAV platform, thath use of GCPs (Ground Control Points), with a more immediate and less expensive scanning method based on direct "geotag" on board the drone (McMahon et al, 2021;Bayanlou & Khoshboresh-Masouleh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to construct a deep learning model suitable for datasets of different sources (or even for different tasks). For example, Bayanlou et al 8 . proposed a common framework and developed a new dataset based on the SAMA-VTOL dataset from a fixed-wing UAV for the performance assessment of multitask learning methods.…”
Section: Introductionmentioning
confidence: 99%